2019
DOI: 10.4314/sajas.v48i5.8
|View full text |Cite
|
Sign up to set email alerts
|

Effect of dietary supplementation with medium chain fatty acids on growth performance, intestinal histomorphology, lipid profile and intestinal microflora of broiler chickens

Abstract: The aim of the present study was to assess the effects of medium-chain fatty acid (MCFA) diet supplementation on growth performance, intestinal histomorphology, serum biochemistry and intestinal microflora of broiler chickens. The study was performed on 180 one-day-old broilers of the same origin (Cobb 500 hybrid), over a 42-day period. They were fed diets supplemented with three treatments: control group (basal diet without supplementation); group with MCFA supplementation; and group with MCFA and coccidiosta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
12
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 29 publications
(33 reference statements)
3
12
1
Order By: Relevance
“…The production results obtained within this research were in accordance with the results of other authors (Šević, 2016;Branković Lazić et al, 2021;Baltić et al, 2018;Milanković et al, 2019). However, anal- Influence of phytobiotics in feed on the cost-effectiveness of broiler production during fattening ysis of performance data (body weight, ADG, FCR and mortality) are essential to calculate the economic efficiency of broiler growth.…”
Section: Resultssupporting
confidence: 92%
“…The production results obtained within this research were in accordance with the results of other authors (Šević, 2016;Branković Lazić et al, 2021;Baltić et al, 2018;Milanković et al, 2019). However, anal- Influence of phytobiotics in feed on the cost-effectiveness of broiler production during fattening ysis of performance data (body weight, ADG, FCR and mortality) are essential to calculate the economic efficiency of broiler growth.…”
Section: Resultssupporting
confidence: 92%
“…Leeson et al [64] and Panda et al [65] reported improved duodenal VH and crypt depth (CD) by MCFAs supplementation in broilers' diet that could be helpful for intestinal development in young birds. High duodenal and ileal villus heights by MCFAs supplementation in birds' diets were also documented by [56,66]. Increasing villus length can increase enzyme production and improve digestion by increasing effective absorbance and enhancing nutrient absorption [67].…”
Section: Discussionmentioning
confidence: 99%
“…Allee et al [ 55 ] reported no significant changes in WG, FI, and feed efficiency of pigs fed 10% MCTs supplemented diet compared to those fed on diets complemented with tallow, pig fat, or corn oil at the same level. Furthermore, the results of Baltić et al [ 56 ] showed that broiler diets supplemented with MCFAs affected the broiler performance positively. Decuypere and Dierick [ 57 ] attributed the improved growth performance to the antibacterial effects of the MCFAs, especially against pathogenic bacteria.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…MCFAs have a smaller molecular size and hence have a lower weight than long-chain FAs, facilitating rapid absorption into the portal vein (Baltić et al, 2017;Hanczakowska, 2017). This characteristic may lead to a decrease in the level of LDL-C, and several previous studies have shown that MCFA decreased LDL-C and increased TG (Baltić et al, 2019;Hill et al, 1990;Sung et al, 2018). Here, the relative weight of the duodenum in the 25HILM group was increased, possibly because of its higher relative length compared with that in the CON group.…”
Section: Discussionmentioning
confidence: 67%